Implementasi model parenting yang responsif terhadap perubahan perkembangan anak usia dini di dusun biyan desa sukomulyo kecamatan pujon kabupaten malang - Syahputra, Rheiga (Maliki Interdisciplinary Journal, 2025)
This research investigates the application of a responsive parenting model in Dusun Biyan, Sukomulyo Village, Pujon District, Malang Regency, and its effects on early childhood development. The study involves ten parents from diverse educational backgrounds and professions, utilizing a qualitative methodology that includes in-depth interviews and observations. Findings reveal that parents in Dusun Biyan actively engage in responsive parenting, characterized by attention, understanding, and responsiveness to their children's needs. Positive interactions between parents and children, demonstrated through participation in play and educational activities, foster an environment conducive to the social, cognitive, and emotional growth of children. Influencing factors for the implementation of responsive parenting encompass parents' educational levels, community social support, and resource availability. Children nurtured in a responsive parenting setting exhibit favorable development outcomes, such as enhanced social skills, improved cognitive functions, and better emotional regulation. The study advocates for training programs and support systems for parents to deepen their understanding of effective parenting practices and to enhance access to educational resources.